THE COMPARATIVE STUDY OF FIQH SIYASAH WITH THE GENERAL PRINCIPLES OF GOOD GOVERNMENT IN INDONESIA - Prawitra Thalib; Bagus Oktafian Abrianto (Arena Hukum, 2019)
Abstrak Asas-Asas Umum Pemerintahan yang Baik saat ini menjadi salah satu dasar penilaian bagi hakim di Peradilan Tata Usaha Negara untuk menguji suatu tindak pemerintah tersebut mengandung unsur kerugian bagi masyarakat atau tidak. Adanya UU 30 Tahun 2014 tentang Administrasi Pemerintahan telah memperluas kompetensi Peradilan Tata Usaha negara dimana obyek gugatan dalam PTUN tidak hanya KTUN (beschikking) akan tetapi juga tindakan faktual dari pejabat atau badan tata usaha negara. Dengan adanya perubahan UU No. 5 Tahun 1986 tentang Peradilan Tata Usaha Negara yaitu UU No. 9 Tahun 2004 dan UU No. 51 Tahun 2009 mempertegas keberadaan Asas-Asas Umum Pemerintahan yang Baik sebagai alasan menggugat di PTUN. Tidak bisa dipungkiri saat ini konsep hukum Islam banyak dipakai dan diterapkan dalam tindakan-tindakan hukum, baik dalam ranah hukum bisnis atau privat maupun hukum publik. Oleh karena itu maka konsep pemerintahan yang baik menurut Islam perlu dikaji secara mendalam, sering disebut dengan konsep fiqh siyasah. Penelitian ini ditujukan untuk meneliti perbandingan antara konsep Asas-Asas Umum Pemerintahan yang Baik di satu sisi dengan konsep fiqh siyasah di sisi yang lain.Â Abstract The General Principles of Good Government are currently one of the assessment bases for the judges in the Administrative Court to examine whether or not actions of the government contains the elements of harm for the community. The existence of Law No.30 of 2014 on Government Administration has expanded the competence of The Administrative Court (PTUN) in which the object of lawsuit in the Administrative Court is not only the Decisions of Administrative (beschikking) but also factual action from official or administrative institutions. With the amendment of Law No.5 of 1986 on the Administrative Court namely Law No. 9 of 2004 and Law No.51 of 2009 affirms the existence of The General Principles of Good Government as one of reasons to sue in the Administrative Court. It is inevitable today that the concept of Islamic law is widely used and applied in legal actions, whether in the realm of business law, private law or public law. Therefore, the concept of good government according to Islam needs to be studied further, often referred to as the concept of fiqh siyasah. This study is aimed to examine the comparison between the concept of The General Principles of Good Government with the concept of fiqh siyasah.